2004
DOI: 10.1182/blood-2003-08-2768
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of casein kinase Iϵ in cytokine-induced granulocytic differentiation

Abstract: Two closely related casein kinase I (CKI) isoforms, CKI␦ and CKI⑀, are ubiquitously expressed in many human tissues, but their specific biologic function remains to be clarified. Here, we provide the first evidence that CKI⑀ is involved in hematopoietic cell differentiation. CKI⑀, but not CKI␦, was down-regulated along with human granulocytic differentiation. The specific down-regulation was observed in granulocyte colony-stimulating factor (G-CSF)-induced cell differentiation of murine interleukin-3 (IL-3)-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 67 publications
(100 reference statements)
2
20
0
Order By: Relevance
“…CSNK1E is a member of the casein kinase I protein family, whose members have been implicated in the control of cytoplasmic and nuclear processes, including DNA replication and repair. The stabilization of components of cytokines and Wnt signaling by CSNK1E might be critical for hematopoietic cell self-renewal (Okamura et al 2004). Interestingly, mutations in a related casein kinase, CSNK1A1, are prevalent in MDS with del(5q), suggesting a role of this gene family in MDS pathogenesis (Schneider et al 2014;Heuser et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…CSNK1E is a member of the casein kinase I protein family, whose members have been implicated in the control of cytoplasmic and nuclear processes, including DNA replication and repair. The stabilization of components of cytokines and Wnt signaling by CSNK1E might be critical for hematopoietic cell self-renewal (Okamura et al 2004). Interestingly, mutations in a related casein kinase, CSNK1A1, are prevalent in MDS with del(5q), suggesting a role of this gene family in MDS pathogenesis (Schneider et al 2014;Heuser et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26]53 To investigate whether Per2 is involved in leukemia, we measured its expression in normal bone marrow and bone marrow from patients with AML. Our results show that Per2 expression is reduced in 42% of AML samples.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report showed that CKI⑀ is essential for granulocytic differentiation. 53 Perhaps the decreased activity of Per2 in leukemic cells, which are blocked in their terminal differentiation, occurs not only by down-regulation of its mRNA but also by a posttranscriptional mechanism such as phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Ba/F3 cells were maintained in RPMI 1640 containing 10% FBS and 15% WEHI-conditioned medium (30). HeLa cells were maintained in DMEM containing 10% calf bovine serum.…”
Section: Cells and Transfectionmentioning
confidence: 99%